Treatment patterns and achievement of the treat-to-target goals in a real-life rheumatoid arthritis patient cohort: data from 1317 patients. (September 2020) - Thomas, Konstantinos; Lazarini, Argiro; Kaltsonoudis, Evripidis; Drosos, Alexandros; Papalopoulos, Ioannis; Sidiropoulos, Prodromos; Tsatsani, Panagiota; Gazi, Sousana; Pantazi, Lina; Boki, Kyriaki A.; Katsimbri, Pelagia; Boumpas, Dimitrios; et al.
Background: Data regarding the real-life predictors of low disease activity (LDA) in rheumatoid arthritis (RA) patients are limited. Our aim was to evaluate the rate and predictors of LDA and treatment patterns in RA. Methods: This was a multicenter, prospective, RA cohort study where patients were evaluated in two different time points approximately 12 months apart. Statistical analysis was performed in order to identify predictors of LDA while patterns of disease-modifying anti-rheumatic drug [DMARDs; conventional synthetic (csDMARD) or biologic (bDMARD)] and glucocorticoid (GC) use were also recorded. Results: The total number of patients included was 1317 (79% females, mean age: 62.9 years, mean disease duration: 10.3 years). After 1 year, 57% had achieved LDA (DAS28ESR<3.2) while 43% did not (34%: moderate disease activity: DAS28ESR ⩾3.2 to <5.1, 9%: high disease activity, DAS28ESR ⩾5.1). By multivariate analysis, male sex was positively associated with LDA [odds ratio (OR) = 2.29 p  < 0.001] whereas advanced age (OR = 0.98, p  = 0.005), high Health Assessment Questionnaire (HAQ) score (OR = 0.57, p  < 0.001), use of GCs (OR = 0.75, p  = 0.037) or ⩾2 bDMARDs (OR = 0.61, p  = 0.002), high co-morbidity index (OR = 0.86, p  = 0.011) and obesity (OR = 0.62, p  = 0.002) were negative predictors of LDA. During follow-up, among active patients (DAS28ESR >3.2), 21% initiated (among csDMARDs users) and 22% switched (among bDMARDs users) their bDMARDs. Conclusion: In a real-life RA cohort, during 1 year of follow-up, 43% of patients do not reach treatment targets while only ~20% of those with active RA started or switched their bDMARDs. Male sex, younger age, lower HAQ, body mass index and co-morbidity index were independent factors associated with LDA while use of GCs or ⩾2 bDMARDs were negative predictors.